A Conceptual Framework about Employees’ Proactive Behavior and Supervisor’s Favorable Evaluation: Moderating Effects of Dissimilarity in Supervisors’ Cultural Dimensions - Rakthin, Sirisuhk; Punnakitikashem, Prattana; Otakanon, Burim; Khin Khin Oo, Nay Chi (Archives of Business Research, 2022)
This study aims to develop a theoretical model of how supervisor’s cultural differences moderate the relationship between proactive behavior of employees and the supervisor’s favorable evaluations. We first review the literature and define the constructs. Then, we describe how the relationship between proactive behavior of an employee and the supervisor’s favorable assessment level could be moderated by the differences between the models of independent or individualistic culture vs. interdependent or collectivistic culture and the cultural tightness-looseness of the supervisor. The conceptual framework and theoretical models of this relationship and moderating effects are proposed. The theoretical model of this study contributes to the organizational and strategic management literature by proposing the moderating effects of supervisor’s cultural differences in assessing different aspects of employee’s proactive behavior.